Density, activity patterns, and habitat selection of Puma (Puma concolor) in the high-altitude plateaus of Tarapacá, Chile - Leichtle, Jorge; Bonacic, Cristian (Therya Notes, 2025)
We investigated the ecology of the puma (Puma concolor) in the high-altitude plateaus of Tarapacá, northern Chile, with a focus on population density, daily activity patterns, and habitat selection. We hypothesized that prey scarcity and human presence would result in low population density, predominantly nocturnal activity, and a preference for shrubland (“tolar”) habitat. Systematic camera-trap surveys were conducted during two seasonal periods in 2012, totaling 1,602 trap-nights. Puma density was estimated using capture-recapture methods based on Maximum Mean Distance Moved (MMDM) and Minimum Convex Polygon (MCP). Activity patterns were analyzed by hour, and habitat selection was assessed using the Ivlev Selection Index and logistic regression. A total of 72 independent detection events were recorded, corresponding to four identified individuals. Density estimates ranged from 0.2 to 0.6 individuals per 100 km²—the lowest reported for Puma concolor in Chile. Eighty percent of detections occurred between 20:00 and 04:59 h, indicating a bimodal nocturnal activity pattern. Shrublands were preferred (Ivlev Index = +0.15), wetlands were avoided (–0.35), and detection probability was higher in areas with over 40% tolar cover. The low population density likely reflects limited wild prey availability and indirect competition with livestock. Nocturnality appears to be a behavioral adaptation to avoid human activity. The broad spatial distribution of detections suggests wide-ranging movements. Although fieldwork was conducted in 2012, ecological conditions have remained relatively stable, supporting the relevance of our findings, despite emerging threats such as infrastructure development and wildlife decline. This study provides essential baseline data on puma ecology in the Tarapacá highlands and supports evidence-based management. We recommend implementing long-term monitoring with telemetry, improving nighttime livestock protection, and conserving tolar corridors to promote puma persistence in high Andean environments.